Episiotomy Scar Endometriosis: A Case Report and Review of Literature. (Indian Journal of Case Reports, 2022)
Abstract Background Endometriosis is defined as the presence and growth of endometrial tissue implants, outside the uterine cavity. It may be pelvic and extra-pelvic sites. Endometriosis in an episiotomy scar is extremely rare but can lead to significant morbidity in patients due to local infiltration. This condition usually presents with clinical triad of history of episiotomy, tender nodule at the scar site and cyclical pain. Case Presentation Here we report one such case of episiotomy scar endometriosis in the perineum of a 30 years young female (P1L1) which presented with swelling and pain in perineal region. The clinical examination and Ultrasonography (USG) corroborate with diagnosis of episiotomy scar endometriosis. Excision was done and histopathological examination confirmed the diagnosis. Conclusion Episiotomy scar endometriosis should always be kept in differential diagnosis when a lady presents with painful perineal swelling which increases during menstruation. This can be diagnosed with clinical and radiological examination. Wide local excision is the treatment of choice. Confirmation of the lesion can be done with histopathological examination. Keywords: Episiotomy scar endometriosis, perineal scar endometriosis, scar endometriosis